2016
DOI: 10.1371/journal.pone.0145398
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Y-Encoded Transcription Factor Zfy2 Is Essential for Sperm Head Remodelling and Sperm Tail Development

Abstract: A previous study indicated that genetic information encoded on the mouse Y chromosome short arm (Yp) is required for efficient completion of the second meiotic division (that generates haploid round spermatids), restructuring of the sperm head, and development of the sperm tail. Using mouse models lacking a Y chromosome but with varying Yp gene complements provided by Yp chromosomal derivatives or transgenes, we recently identified the Y-encoded zinc finger transcription factors Zfy1 and Zfy2 as the Yp genes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…One of the most generally accepted hypotheses is that the cytoplasmic continuity they provide equalises the genomic contents of postmeiotic cells [7], thus rendering postmeiotic cells phenotypically diploid [8]. Support for this hypothesis comes from the observation that, in postmeiotic cells, X-encoded transcripts pass through intercellular bridges in the form of protein-messenger RNA (mRNA) complexes [9] and that, in general, both the X and Y chromosomes encode postmeiotically expressed genes that are essential for sperm cytodifferentiation and function, e.g., [10][11][12]. Consequently, it is undeniable that postmeiotic equalisation of X-and Y-encoded gene products across the syncytium must be essential for fertility in mammals.…”
Section: A Bridge Over Uncharted Watersmentioning
confidence: 99%
“…One of the most generally accepted hypotheses is that the cytoplasmic continuity they provide equalises the genomic contents of postmeiotic cells [7], thus rendering postmeiotic cells phenotypically diploid [8]. Support for this hypothesis comes from the observation that, in postmeiotic cells, X-encoded transcripts pass through intercellular bridges in the form of protein-messenger RNA (mRNA) complexes [9] and that, in general, both the X and Y chromosomes encode postmeiotically expressed genes that are essential for sperm cytodifferentiation and function, e.g., [10][11][12]. Consequently, it is undeniable that postmeiotic equalisation of X-and Y-encoded gene products across the syncytium must be essential for fertility in mammals.…”
Section: A Bridge Over Uncharted Watersmentioning
confidence: 99%
“…Some studies have shown that reducing the level of Zfx/Zfy mRNA expression will make the physiological function of X/Y sperm worse, which can influence offspring gender [14,17,[20][21][22]. Zfy is closely related to sperm head and tail formation and neck development [23], which is highly expressed between meiosis I and II. It can regulate sperm morphology and ROSI efficiency, and promotes second meiosis [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Specific Y genes have been identified that control specific aspects of spermatogenesis [73, 102, 104, 108, 109], but to date, no specific X gene has been identified that causes a sex chromosome effect. Because of the advent of more efficient gene targeting methods, we expect this situation to change soon.…”
Section: Discussionmentioning
confidence: 99%
“…The first cross involves a commercially available Sxr a mutation that involves translocation of Y short arm (Yp) genes to the tip of the X or Y PAR and will establish if the SCE involves Yp genes that map to Sxr a [104]. If this is not the case, the second cross utilizing a Y deletion (Y d1 ) should provide confirmation that multi-copy NPY genes are involved.…”
Section: Identifying Npy Genes That Cause Direct Scesmentioning
confidence: 99%